Special Issue: Research in economics and sport management - Gálvez Ruiz, Pablo; Fernández-Gavira, Jesús; García-Fernández, Jerónimo; García-Villar, Jaume (Intangible Capital, 2017)
The sport currently represents one of the most deeply rooted social phenomena, which also have a high capacity for mobilization. It has a social significance and also an important economic dimension that is difficult to quantify accurately, but is considered an engine of development, which implye indirectly to a large number of different activities that include other industries, taking in this regard an important crosscutting. In this context, Intangible Capital Journal launches this monograph in which research from diverse perspectives of the economy of sport is included, thus highlighting the importance and impact it has on different sectors are integrated. Therefore, the objective of this issue is to advance in the study of sports economics by joining forces and bringing new products through research.
Número especial: Investigación en economía y gestión del deporte
Keywords: economy; management; sport; Emerging; Scopus